2020
DOI: 10.1038/s41598-020-76535-y
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment of circadian rhythms of locomotor activity by ambient temperature cycles in the dromedary camel

Abstract: In the dromedary camel, a well-adapted desert mammal, daily ambient temperature (Ta)-cycles have been shown to synchronize the central circadian clock. Such entrainment has been demonstrated by examining two circadian outputs, body temperature and melatonin rhythms. Locomotor activity (LA), another circadian output not yet investigated in the camel, may provide further information on such specific entrainment. To verify if daily LA is an endogenous rhythm and whether the desert Ta-cycle can entrain it, six dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Therefore, these insignificant changes in Ta do not explain why, at the transition from night to day, resting camels on sternal recumbency get up suddenly and start their daily activity and why, at the transition from day to night, the activity of the camels is unexpectedly interrupted, entering instantly into the nocturnal rest phase. In our previous studies (El Allali et al 2013;Farsi et al 2020), we have shown that, in the camel, the central circadian clock and its three outputs, the body temperature, locomotor activity and melatonin secretion rhythms, are entrained by Ta cycle. The no-involvement of Ta in the triggering of the activity onset and offset in the present study is not inconsistent with the previous demonstration of its entrainment of the circadian clock.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, these insignificant changes in Ta do not explain why, at the transition from night to day, resting camels on sternal recumbency get up suddenly and start their daily activity and why, at the transition from day to night, the activity of the camels is unexpectedly interrupted, entering instantly into the nocturnal rest phase. In our previous studies (El Allali et al 2013;Farsi et al 2020), we have shown that, in the camel, the central circadian clock and its three outputs, the body temperature, locomotor activity and melatonin secretion rhythms, are entrained by Ta cycle. The no-involvement of Ta in the triggering of the activity onset and offset in the present study is not inconsistent with the previous demonstration of its entrainment of the circadian clock.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study was formulated on a discontinuous ethogram and, furthermore, was limited to only two consecutive days of recording. Farsi et al (2018), Farsi et al (2020) provided the first demonstration of diurnal activity in dromedary camel. Recording of locomotory activity rhythm has been difficult due to several technical constraints meet in large mammals and particularly in this species (El Allali et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological rhythm mainly controlled by the SCN is endogenous but it is also affected by the environmental cycles. There have been some studies that suggest that the circadian rhythm of locomotor activity in mice and dromedary camels is affected by the ambient temperature cycle [43,44]. Although, the effect of the ambient temperature cycle is weaker than the light/dark cycle [44], which are affected by the range, amplitude, and time of the ambient temperature cycle.…”
Section: Discussionmentioning
confidence: 99%